The Induction of a Permissive Environment to Promote T Cell Immune Evasion in Acute Myeloid Leukemia: The Metabolic Perspective - Mougiakakos, Dimitrios (Frontiers in Oncology, 2019)
Acute myeloid leukemia (AML) is the acute leukemia with highest incidence amongst adults. Despite significant improvements in understanding the genomic landscape and the introduction of novel drugs long-term outcome remains unsatisfactory. To date, immunotherapeutic approaches have heralded a new era in cancer treatment. The success of allogeneic hematopoietic stem cell transplantation in AML highlights the disease’s immunoresponsiveness with several immunotherapeutic applications being currently under clinical evaluation that include immune checkpoint blockade, T-cell engaging antibodies, and genetically engineered T-cells. However, immunoevasive mechanisms employed by AML blasts severely hamper our endeavours. A better under-standing of the underlying mechanisms remains a prerequisite for improving treatment efficacy. One of the cancer cells’ hallmark is metabolic reprogramming that was introduced by Otto War-burg’s seminal studies during the beginnings of the last century. Nowadays, it is well established that metabolic adaptation is not just an epiphenomenon during oncogenesis but rather a necessity for tumor development and progression. Furthermore, accumulating data suggest an important role of aberrant tumor cell metabolism for immune escape. AML blasts display a number of metabolic alterations that could be linked to immunoregulation and range from competition over substrates, abundant release of bioactive metabolites, and an overall microenvironmental metabolic remodelling that favours the induction or survival of immunoregulatory cell subsets such as regulatory T-cells. In this review, we outline the immunoevasive character of the AML blasts’ bioenergetics, set it into context with oncogenic mutations, and discuss potential suitable countermeasures and their limitations.